Effects of blood parasite infections on spatiotemporal migration patterns and activity budgets in a long‐distance migratory passerine - Emmenegger, Tamara (Ecol Evol, 2020)
How blood parasite infections influence the migration of hosts remains a lively debated issue as past studies found negative, positive, or no response to infections. This particularly applies to small birds, for which monitoring of detailed migration behavior over a whole annual cycle has been technically unachievable so far. Here, we investigate how bird migration is influenced by parasite infections. To this end, we tracked great reed warblers (Acrocephalus arundinaceus) with multisensor loggers, characterized general migration patterns as well as detailed flight bout durations, resting times and flight heights, and related these to the genus and intensity of their avian haemosporidian infections. We found migration distances to be shorter and the onset of autumn migration to be delayed with increasing intensity of blood parasite infection, in particular for birds with Plasmodium and mixed‐genus infections. Additionally, the durations of migratory flight bout were prolonged for infected compared to uninfected birds. But since severely infected birds and particularly birds with mixed‐genus infections had shorter resting times, initial delays seemed to be compensated for and the timing in other periods of the annual cycle was not compromised by infection. Overall, our multisensor logger approach revealed that avian blood parasites have mostly subtle effects on migratory performance and that effects can occur in specific periods of the year only.